Iodine Uptake and Prostate Cancer in the TRAMP Mouse Model - Paloma Olvera-Caltzontzin; Guadalupe Delgado; Carmen Aceves; Brenda Anguiano (BMC, 2013)
Abstract Iodine supplementation exerts antitumor effects in several types of cancer. Iodide (I−) and Iodine (I2) reduce cell proliferation and induce apoptosis in human prostate cancer cells (LNCaP and DU-145). Both chemical species decrease tumor growth in athymic mice xenografted with DU-145 cells. The aim of this study was to analyze the uptake and effects of iodine in a preclinical model of prostate cancer (transgenic adenocarcinoma of the mouse prostate [TRAMP] mice/SV40-TAG antigens), which develops cancer by 12 wks of age. 125I− and 125I2 uptake was analyzed in prostates from wild-type and TRAMP mice of 12 and 24 wks in the presence of perchlorate (inhibitor of the Na+/I− symporter [NIS]). NIS expression was quantified by quantitative polymerase chain reaction (qPCR). Mice (6 wks old) were supplemented with 0.125 mg I− plus 0.062 mg I2/mouse/day for 12 or 24 wks. The weight of the genitourinary tract (GUT), the number of acini with lesions, cell proliferation (levels of proliferating cell nuclear antigen [PCNA] by immunohistochemistry), p53 and p21 expression (by qPCR) and apoptosis (relative amount of nucleosomes by enzyme-linked immunosorbent assay) were evaluated. In both age-groups, normal and tumoral prostates take up both forms of iodine, but only I− uptake was blocked by perchlorate. Iodine supplementation prevented the overexpression of NIS in the TRAMP mice, but had no effect on the GUT weight, cell phenotype, proliferation or apoptosis. In TRAMP mice, iodine increased p53 expression but had no effect on p21 (a p53-dependent gene). Our data corroborate NIS involvement in I− uptake and support the notion that another transporter mediates I2 uptake. Iodine did not prevent cancer progression. This result could be explained by a strong inactivation of the p53 pathway by TAG antigens.